TREATMENT OPTIONS FOR GUILLAIN-BARRE SYNDROME (GBS) - A COMPARATIVE ASSESSMENT OF TREATMENT EFFICACY BETWEEN INTRAVENOUS IMMUNE GLOBULIN (IVIG) WITH PLASMAPHORESIS - Muhammad, Wasim Wali; Yousaf, Muhammad Ali; Ullah, Muhammad Usman; Khan, Ahmad Mushtaq; Yousaf, Muhammad Jawad; ., Manzoor Qadir (Pakistan Armed Forces Medical Journal, 2011)
Objective: To compare the therapeutic efficacy of Intravenous immune globulin (IVIG) with Plasma exchange (plasmaphoresis) in patients of Acute Inflammatory Demyelinating Polyneuropathy i.e. Guillain-Barre syndrome (GBS).Study design: Randomized Controlled Trial (RCT)Place and duration of the study: The study was of 12 months duration conducted at Department of Medicine, Neurology Unit of Military Hospital Rawalpindi from Jun 2008 to Jun 2009.Subjects and methods: 60 Patients of GBS were randomly assigned to two treatment groups. Group A received Intravenous immune globulin (IVIG) and Group B Plasma Exchange. Patient's functional status according to London scale grade was assessed at the time of admission and at 02 and 04 weeks after giving treatment. Improvement in mean London scale Grades in each group was calculated at different weeks from baseline and then both groups were compared to each other.Results: In each group there was significant improvement (P-value< 0.001) from baseline-2weeks and baseline-4 weeks. But when compared to each other both the groups had comparable improvement (p-value> 0.05).Conclusions: Both IVIG and Plasma Exchange have equal therapeutic efficacy in the treatment of patients ofGBS.